The economic costs of selecting medical students: An Australian case study. Issue 7 (24th April 2020) - Foo, Jonathan; Rivers, George; Allen, Louise; Ilic, Dragan; Maloney, Stephen; Hay, Margaret
Abstract: Context: The design of selection methods must balance, amongst a range of factors, the desire to select the best possible future doctors with the reality of our resource‐constrained environment. Examining the cost of selection processes enables us to identify areas in which efficiencies may be gained. Methods: A cost description study was conducted based on selection for 2018 entry into medical school directly from secondary school. The perspectives of applicants, volunteer interviewers and the admitting institution were considered. Costs were modelled based on the Monash University (Australia) selection process, which uses a combination of secondary school matriculation score, aptitude test score (Undergraduate Medicine and Health Sciences Admission Test) and multiple mini‐interview score. A variety of data sources were utilised, including bespoke surveys, audit data and existing literature. All costs are expressed in 2018 Australian dollars (AU$). Applicant behaviours in preparing for selection tests were also evaluated. Results: A total of 381 of 383 applicants returned the survey. Over 70% of applicants had utilised commercial preparation materials. The median total cost to applicants was AU$2586 (interquartile range [IQR] AU$1574‐3999), including costs to both prepare for and attend selection tests. Of 217 volunteer interviewers, 108 returned the survey. These were primarily health professional clinicians at a mid‐career stage. The median total cost to interviewers was AU$452 (IQR AU$252‐715) for participation in a half‐day interview session, largely due to the loss of income. The cost to the admitting institution was AU$269 per applicant, accounted for by the costs of equipment and consumables (52%), personnel (34%) and facilities (14%). Conclusions: The costs of student selection for medical school are substantial. Understanding costs facilitates achievement of the objective of selecting the desired future medical workforce within the constraints of the resources available. Opportunities for change may arise from changes in applicant preparation behaviours, opportunities for economies of scale, and efficiencies driven by technological solutions. Abstract : What does it take to get into medical school? Money for one thing. The authors demonstrate that, in Australia, students spend AU$2, 586 on preparation, attendance. The universities to which they apply spend AU$269 per applicant, money that is likely to be recouped if selection can avoid student attrition.